Dampak Nilai Waktu Uang Dalam Penilaian Proyek Insfrastruktur Pemerintahan Daerah - armayani, Dinda putri; Julianti, Faizah Dwi; Fauzi, Achmad; Annuri, Dina Fitria; Putra, Dimas Listyanto; Nurambarwati, Dwi (Jurnal Manajemen dan Pemasaran Digital, 2023)
Local government infrastructure project appraisals that take into account the community's time value of money have a significant impact on quality of life, the economy, the environment, and community participation. Time value of money refers to the time available for communities to enjoy the facilities or services provided by an infrastructure project. This article outlines the impact of time value for money in local government infrastructure project appraisal, including improved quality of life, support for local tourism, economic development, improved social welfare, more positive environmental impacts, and community participation in decision-making. A comprehensive infrastructure project appraisal should consider these factors to ensure the success and sustainability of the project. The results of this discussion use qualitative methods by using literature review journals from Google, Google Scholar, Researchgate, and other online media.